FRI0205 Analysis of the Characteristics of Patients with Chronic Back Pain Referred from Primary Care to a Rheumatology Service. (9th June 2015) - Lόpez Medina, C.; Calvo Gutiérrez, J.; Jiménez Gasco, R.; Castro Villegas, M.C.; Ortega Castro, R.; Font Ugalde, P.; Escudero Contreras, A.; Collantes Estévez, E.
Abstract : Background: In recent years it has become increasingly important to design strategies for the detection of patients with Axial Spondyloarthritis (axial SpA), thus allowing us to prescribe appropriate medication to avoid structural damage. However, some studies have shown a lack of agreement on the appreciation of back pain characteristics by Primary Care specialists. Because of this, sometimes the derivation to a Rheumatology Service is not adequate. Objectives: To analyse the clinical, analytical and radiographical characteristics of patients with chronic back pain (CBP) and younger than 45 years old referred from Primary Care (PC) to a Rheumatology service. Methods: A descriptive analysis which included 95 patients referred from Primary Care with chronic back pain and younger than 45 years old who underwent a full clinical and analytical examination which aimed to determine Spondyloarthritis criteria (sacroiliac joints X-ray, HLAB-27) in each patient. The patients also answered an anamnesis undertaken by a specialist clinician in Rheumatology, the aim of which was to determine in each patient the presence of items which define the inflammatory back pain (IBP) by ASAS. In this way, patients were classified in two different groups: a) those that meet IBP criteria, and b) those that do not meet IBP criteria (non-IBP). An analysis of the connection between the two groups of patients with different variables took place. Results: Out of the 95 patients, 35 of them (38.9%) were classified as IBP and 55 (61.1%) as non-IBP. Table 1 represents the most important clinical and analytical characteristics from DLI patients, compared with non-DLI patients. Also, the table shows the results of the bivariate and multivariate logistic regression. The multivariate logistic regression model showed that patients with pathologic SI joints X-ray have a 78.78 higher risk of having IBP as well as a 4.19 increased probability in patients with a positive result in HLA-B27. Out of the 35 IBP patients, 27 of them (77.14%) met the ASAS criteria for axial SpA, with a 19.82 higher risk of having IBP. Conclusions: This research suggests that IBP is the most distinctive clinical characteristic of axial SpA and it is defined as an accurate criterion for referring patients with chronic back pain to a Rheumatology service. Disclosure of Interest: None declared